Analysis of seasonal tendencies in pediatric Henoch–Schönlein purpura and comparison with outbreak of infectious diseases. Issue 36 (September 2018) - Hwang, Hyun Ho; Lim, In Seok; Choi, Byung-Sun; Yi, Dae Yong
Abstract : Abstract: Henoch–Schönlein purpura (HSP) is one of the most common vasculitis in children. This study was aimed at identifying seasonal trends and epidemiologic features of pediatric HSP patients through public data to analyze the correlation of HSP and prevalence of a specific respiratory or enteric virus. We extracted information on pediatric HSP patients categorized into 4 age groups and data on 8 respiratory and 4 enteric viruses were extracted from national data. We used the decomposition of time series analysis and correlation analysis to identify the incidence of HSP and the prevalence of each virus. From 2013 to 2016, 16, 940 patients under the age of 18 were diagnosed with HSP in Korea, 6203 (36.6%) were diagnosed with HSP in middle childhood. Spring had the largest number of patients (5252, 31.0%), and summer had the smallest number of patients (3224, 19.0%). The largest and smallest number of cases occurred in March (1949, 11.5%) and August (959, 5.7%), respectively. However, among the adolescents, more patients were diagnosed in the summer (985, 24.8%) than in the fall (760, 19.1%). The positive detection counts of most viruses showed apparent seasonal variations. Depending on the age group, the epidemic patterns of influenza and rotaviruses were temporally and statistically similar to that of HSP. We have confirmed that the occurrence of pediatric HSP in Korea shows a seasonal tendency, which is age-dependent and related to exposure to infectious agents and suggest some respiratory or enteric viruses may play an important role in pathophysiology.